“Like Having a Really bad PA”: The Gulf between User Expectation and Experience of Conversational Agents. - Luger, Ewa; Sellen, Abigail (Proceeding of CHI 2016, 2016)
The past four years have seen the rise of conversational agents (CAs) in everyday life. Apple, Microsoft, Amazon, Google and Facebook have all embedded proprietary CAs within their software and, increasingly, conversation is becoming a key mode of human-computer interaction. Whilst we have long been familiar with the notion of computers that speak, the investigative concern within HCI has been upon multimodality rather than dialogue alone, and there is no sense of how such interfaces are used in everyday life. This paper reports the findings of interviews with 14 users of CAs in an effort to understand the current interactional factors affecting everyday use. We find user expectations dramatically out of step with the operation of the systems, particularly in terms of known machine intelligence, system capability and goals. Using Norman's ‘gulfs of execution and evaluation’ [30] we consider the implications of these findings for the design of future systems.